Tropical Almond–Based Yogurt Fortified with Celery: A Functional Food for Lipid Profile Improvement and Anti-Inflammatory Support - Soraya Habibi; Einstivina Nuryandani; Nanik Suhartatik; Merkuria Karyantina; Fadilah Husnun; Akhmad Mustofa; Pundhi Ludiani Hartiwi (Journal of Applied Agricultural Science and Technology, 2026)
The development of yogurt as a functional food has gained significant attention. Tropical almond (Terminalia catappa) is rich in fat and protein, while celery is known for its antioxidant, anti-inflammatory, hypolipidemic, and hypoglycemic properties. This study investigated the development of functional yogurt made from tropical almond milk fortified with celery extract. It employed a Completely Randomized Design (CRD) with varying celery extract concentrations (1%, 2%, and 3%) and fermented for 14, 17, and 20 hours. The results showed that after 17 hours of fermentation, total acid-producing bacteria reached 7.87 log CFU (colony forming unit)/ml, exhibiting acceptable sensory attributes and enhanced antioxidant activity. In vivo tests on Wistar rats revealed significant reductions in malondialdehyde (MDA) and interleukin-6 (IL-6) levels, which indicate anti-inflammatory and lipid-lowering effects. These findings highlight the potential of tropical almond-based yogurt as a novel functional food, paving the way for sustainable dietary interventions targeting metabolic health.